Decoding JFT: a multifunctional fluorescence probe for sulfite and viscosity insights - Han, Hua; Han, Bin; Peng, Yongjin; Liu, Yuling (Frontiers in Chemistry, 2025)
This study focuses on a multifunctional fluorescence probe JFT based on the FRET (Fluorescence Resonance Energy Transfer) and TICT (Twisted Intramolecular Charge Transfer) mechanism. JFT combines an electron donor and an acceptor, enabling it to detect sulfite and monitor intracellular viscosity. When reacting with sulfite, its electronic structure changes, turning off FRET and altering fluorescence wavelength and intensity. In different viscosity environments, the rotation of carbon-carbon bonds in the electron acceptor structure of JFT varies, affecting non-radiative transition pathways and fluorescence intensity. Theoretical calculations based on TDDFT reveal the electron distribution changes before and after the reaction with sulfite species, consistent with experimental phenomena. These findings deepen the understanding of the FRET mechanism of fluorescence probes and offer theoretical guidance for the design of more efficient fluorescence probes.